The Gender Pay Gap and Irish higher education: University of Galway, a case study - Laura Loftus; Niall Madden; P. Anne Scott; Aoife Cooke; Nicola McNicholas (Administrative Sciences, 2023)
This article presents the first comprehensive, multi-year study of the Gender Pay Gap (GPG) for a single higher education institution in Ireland. University of Galway has reported on its GPG annually since 2018. It identifies the key findings of these reports, focusing particularly on the 2022 report, while also highlighting trends and learnings from other years' data. Staff cohorts are disaggregated, and details on the mean and median GPG are provided for each. The major contributors to the GPG at University of Galway are identified. These contributors also apply to the Irish Higher Education system more broadly. This study reveals that the mean GPG at University of Galway is driven by academic grades and the median GPG is driven by Professional Managerial and Support Service Staff grades, and that long-term sustained interventions will be required to narrow the gender pay gap at University of Galway.
Keywords: 350; case study; gender equality; gender pay gap; higher education institutions; Irish education